Evaluation of Air Pollution by Heavy Metals on Bab El Oued Zone of Algiers - Belamri, M.; Benrachedi, K. (Asian Journal of Chemistry, 2010)
The present study consists in analyzing the quality of the air in the capital. LVS pump (low volume sampler) was used for the collection of the samples in the district of Bab El Oued in Algiers characterized by the presence of a hospital and an incinerator of medical and different other waste as well as a strong density of traffic cars. The aerosols were taken at height of 3 m of the ground in total suspended particulate (TSP) mode. The samples have been analyzed by EDXRF (energy dispersive X-ray fluorescence). The experimental results show that the daily content of TSP are above limit of the target value 50 μg/m3. The TSP are respon-sible for the transport of toxic heavy metals such as Cd, Pb, Cr and Ni.